Editor's Choice – Delays to Surgery and Procedural Risks Following Carotid Endarterectomy in the UK National Vascular Registry. Issue 4 (October 2016) - Loftus, I.M.; Paraskevas, K.I.; Johal, A.; Waton, S.; Heikkila, K.; Naylor, A.R.; Cromwell, D.A.
Abstract : Objective: Guidelines recommend that patients suffering an ischaemic transient ischaemic attack (TIA) or stroke caused by carotid artery stenosis should undergo carotid endarterectomy (CEA) within 14 days. Method: The degree to which UK vascular units met this standard was examined and whether rapid interventions were associated with procedural risks. The study analysed patients undergoing CEA between January 2009 and December 2014 from 100 UK NHS hospitals. Data were collected on patient characteristics, intervals of time from symptoms to surgery, and 30-day postoperative outcomes. The relationship between outcomes and time from symptom to surgery was evaluated using multilevel multivariable logistic regression. Results: In 23, 235 patients, the median time from TIA/stroke to CEA decreased over time, from 22 days (IQR 10–56) in 2009 to 12 days (IQR 7–26) in 2014. The proportion of patients treated within 14 days increased from 37% to 58%. This improvement was produced by shorter times across the care pathway: symptoms to referral, from medical review to being seen by a vascular surgeon, and then to surgery. The spread of the median time from symptom to surgery among NHS hospitals shrank between 2009 and 2013 but then grew slightly. Low-, medium-, and high-volume NHS hospitals all improved their performance similarly. Performing CEA within 48 h of symptom onset was associated with a small increase in the 30-day stroke and death rate: 3.1% (0–2 days) compared with 2.0% (3–7 days); adjusted odds ratio 1.64 (95% CI 1.04–2.59) but not with longer delays. Conclusions: The delay from symptom to CEA in symptomatic patients with ipsilateral 50–99% carotid stenoses has reduced substantially, although 42% of patients underwent CEA after the recommended 14 days. The risk of stroke after CEA was low, but there may be a small increase in risk during the first 48 h after symptoms.